Emotional competence profile in a higher education students sample - Veiga-Branco, Augusta (2011)
Recent research emphasizes the relationship between emotional responses, cognitive functioning and learning (Ruthig et al., 2007; Chung, I., 2010), and others authors presented emotional intelligence correlated with better academic performance but not with the highest levels of intelligence quotient (Barchard, 2003; Izard, 2001; O’Connor 2003; in Mayer, J., Roberts, and Barsade, 2008). Aim: to define the Emotional Competence profile in higher education students. Method: A cross-sectional survey was carried out in a probabilistic sample including 461 students of higher education from five schools of Polytechnic Institute of Bragança, Portugal. The instrument was based on the model of Emotional Competence developed by Veiga-Branco (2004, 2007). Data was analyzed using descriptive statistics. Factor analysis was used to identify capacities. Additionally, a multiple regression analysis was conducted to determine the relationship between capacities and Emotional Competence and to establish the capacities that were the strongest predictors of Emotional Competence. All senior students had participated in this study, about 33.6% male and 66.2% female, aged between 17 and 39 years old. Conclusions/Results: Five competencies were identified in this study. The ranking of the correlations was as follows: Emotions Management in Group (r=0.789; p<0.001), Empathy (r=0.774; p<0.001), Self-motivation (r=0.767; p<0.001), Emotions Management (r=0.760; p<0.001), and Self-conscience (r=0.700; p<0.001). The Cronbach Alpha for Internal Consistency obtained for each of the capacities was as follows: Emotions Management in Group (0.880), Emotions Management (0.764), Self-motivation (0.784), Empathy (0.849) and Personal Emotions Management (0.759). The estimated regression model includes, Emotions Management in Group, Empaty, Self Motivation, and Emotion Management that represents 96,8% of the variance in Emotional Competencies.